Pengembangan Buku Ajar Tematik pada Subtema Indahnya Keberagaman Budaya Negeriku - Fitriani, Effi; Rusdy A. Siroj; Siti Julaeha (Jurnal Serambi Ilmu, 2025)
This study aims to develop an integrated thematic textbook for the sub-theme The Beauty of My Country’s Cultural Diversity for fourth-grade students at SD Negeri 5 Kota Pagar Alam that is valid, practical, and effective. The research employed a Research and Development (R&D) method using the Rowntree development model, consisting of three main stages: planning, preparation for writing, and writing-editing. Product evaluation was conducted using Tessmer’s formative evaluation model, which includes expert review, one-to-one evaluation, small group evaluation, and field testing. The research subjects were 30 fourth-grade students, with validation carried out by material, language, and design experts. The results indicated that the textbook achieved a high validity level after the revision stage. The practicality test obtained an average score of 80% with positive feedback from students. The effectiveness test showed an improvement in learning outcomes with an N-gain score of 0.76 (high category) and student activeness reaching 90% (active category). These findings suggest that the developed textbook is feasible for use and can improve both learning outcomes and student engagement in thematic learning.